(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines a wide variety of typologies of institutions of representation. They are especially important during the period of democratization of the political system of Kyrgyzstan as a sovereign state. The purpose of the article is to analyze typologies that develop existing ones and supplement the theory of constitutional law with new knowledge. Attention is drawn to the typology of concepts that are formulated in science on the basis of democracy, the relationship between various branches and institutions of government - presidential republic, parliamentary republic, etc. The analysis also drew attention to the problems of democratization of the public administration system, which is linked to the implementation of the functions of representative bodies. In the article, the methodology was built on the principles of dialectics, taking into account specific private scientific methods of analogy, comparison, and the structural method. The conclusions presented in the article are of practical importance for their use in the work of government bodies in the development of national programs and concepts.